Seja homem! : construção de masculinidade na revista Men’s health Brasil - Seixas, Rebeca Bruno da Silva (2012)
The objective of this research was the perception of the masculinity role model which is predominant in the content from Men s Health Brazil magazine and how it is transmitted through such content. Considering the increasing segmentation of the magazine market and the rising number of vehicles that approach the issue of body and health, this publication is presented in a different way as it escapes from the traditional model for men s magazines once it grasps a series of elements which, after analysis, have been identified as components of a construction script for an ideal masculinity model, cast by a quite clear view of what a healthy and successful man should be like (in his personal and social life). With the slogan Living better is easy , the publication guides the construction of its readers masculinity based on truth-speeches mainly legitimated in the sphere of scientific knowledge (such as researches from different universities and the collaboration of professionals from various areas in the elaboration of articles), instructing its readers in several areas from the male experience, from body care and its figure to their everyday living with women and other men. In shaping this ideal model of being a man, Men s Health also brings a series of values on what it is to be a man, which concern the necessity of being virile, competitive, healthy, good in bed , independent and owner of their world. Notwithstanding all of these aspects hold a close approximation to elements that have already been approached by gender theory as belonging to the patriarchal masculinity model. Through the theoretical productions of Michel Foucault on discipline, norm and body and from the complementing to his theory proposed by Anthony Giddens, which is about the reflexive identity embodiment, I have sought to understand how the magazine elaborates its speech in a way that it shapes the reader into a worldwide accepted standard (once this publication is available in several countries) in relation to a hegemonic masculinity. The latter, on its own, as proposed by Robert/Raewyn Connell, is constructed through processes of socialization of the access to means of communication, which exhibit a masculinity that is stated in the differentiation of other masculinity assortments, in the case of Men s Health, the masculinity of men who do not fit in the physical model advertised by the magazine.